Survey on gap filling algorithms in Landsat 7 ETM+ images - Abduljabar, Asmaa Sadiq (Asian Research Publishing Network (ARPN), 2014)
In remote sensing images the gapping is a known phenomenon. There are several reasons for image gaps, e.g. shadowed area for SAR data sets, cloud coverage for optical imagery and instrument errors such as SLC-off failure. On May 13, 2003 the Scan Line Corrector (SLC) of Landsat 7 Enhanced Thematic Mapper Plus (ETM+) sensor failed permanently causing around 20% of pixels per scene not scanned which become an obstacle and limitation for scientific applications of Landsat ETM+ data. Therefore, reconstruction of gap regions is an important issue in remote sensing image processing. This paper presents an inclusive review of methodologies that have been used to recover the gaps in Landsat7 ETM SLC-off images and the studies have been performed in this area. Then, the paper presents the derived conclusions and the directional to more efficiently researchs on Landsat7 SLC-off reconstruction.